Estudo de envelhecimento e propriedades mecânicas de compósito epóxi reforçado com tecido plano de kevlar e híbrido vidro/kevlar - Valença, Silvio Leonardo (2014)
The epoxy resin has a widespread use in the manufacture of polymer composites to obtain various elements of structural engineering. The overall objective of this research is to evaluate the effect of reinforcing fabric architecture fiber-based Kevlar 49 and glass S on the mechanical performance of composites with epoxy matrix. It was observed that the mechanical performance of the epoxy resin and the composite, after natural aging and in seawater at a temperature of 70 ° C. Three architectures are designed for the production of tissue related to the structural reinforcement of the composite element: only aramid (Kevlar 49), and hybrid Kevlar 49 and glass S; varying the type of yarn and intertwining of the composition (fiber content in percentage) in each frame. The composite plates were made by hand casting process with epoxy matrix reinforced with woven fabrics of Kevlar fiber and Kevlar hybrid/glass, according to an innovative architecture. The mechanical properties of the composites were determined by tensile, bending and impact carried out in parallel and perpendicular to the warp direction. We used scanning electron microscopy to observe the reinforcement and matrix fractures after the mechanical tests. The composites with hybrid structure of Kevlar/glass on reinforcing fabric showed the best results with respect to the specific strength and impact energy.